Green Composites Processing, Characterisation and Applications for Textiles - Muthu, Subramanian Senthilkannan; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book highlights the processing, characterization and applications of various green composites. Composites are known for their unique properties, which are derived by combining two or more components. This yields properties such as greater strength and rigidity than that of the individual components, as well as reduced weight. To help achieve such outcomes, the book discusses the potential applications of hybrid bio-composites and sisal-fiber-reinforced epoxidized non-edible oil-based epoxy green composites.
Natural Fiber Based Hybrid Bio-Composites: Processing, Characterization and Applications -- Processing of Green Composites -- Sisal Fibers Reinforced Epoxidized Non-edible Oils Based Epoxy Green Composites and its Potential Applications.
Keywords: Manufactures; Ceramic materials; Sustainability; Industrial Management; Environmental engineering; Biotechnology; Bioremediation; Agriculture -- Economic aspects; Machines, Tools, Processes; Ceramics; Sustainability; Industrial Management; Environmental Engineering/Biotechnology.; Agricultural Economics